A review of novel biological tools used in screening for the early detection of lung cancer. Issue 1005 (5th July 2009) - Ghosal, R; Kloer, P; Lewis, K E
Abstract : Lung cancer is the most common cancer worldwide and causes more deaths per year than any other cancer. It has a very poor 5-year survival rate of 8–16%, partly because of comorbidity preventing curative treatments but mainly because of the disease presenting with symptoms only when it is at an advanced and incurable stage. When lung cancer is detected earlier and is amenable to radical treatments such as potentially curative surgery and radical radiotherapy, 5-year survival rates are much higher (up to 67%). Therefore reliable detection of lung cancer at this earlier (usually asymptomatic) stage of disease should be an important way to improve outcomes. This review discusses the principles of screening with respect to lung cancer, concentrating mainly on the biological modalities used to detect it. The lack of impact achieved by early studies using sputum cytology (in conjunction with chest radiographs) is described, and then newer technology used to measure other biomarkers in sputum, serum, exhaled breath and bronchial mucosa to diagnose (early) lung cancer is detailed. Many techniques show promise, but debate continues about which population to screen and what is the most (cost) effective modality to use. Moreover, no single biomarker or combination of biomarkers in screening has yet been shown to reduce lung cancer mortality in large prospective randomised studies.